The fablabs in the heart of the city: the specificities of places in French-speaking Africa - (:unkn) unknown (My University, 2020)
Fablabs have been flourishing in France and around the world for a few years and are attracting growing interest. Although many studies have been conducted on these spaces in Europe or in developed countries, little research has been conducted on Africa. Our objective is then to ask ourselves about the specificities of the fablabs of French-speaking Africa that are the subject of our study, and to shed some light on these third-places. Thanks to a series of interviews with the fabmanagers of these places, we show that, even if these spaces have features in common with their counterparts in the North, they present a strong characteristic of digital acculturation, destined to specific needs, and focused on identified populations such as young people, artisans and farmers, women. A comparative analysis of French and African places is also proposed in order to identify a typology.
Keywords: African Research